Femoral Neck Stress Fracture of a Male, Healthy Marathon Runner – Case Report and Literature Review - Weinrich, Luise; Dahne, Michael; Lindner, Tobias; Stöckle, Ulrich; Tsitsilonis, Serafeim (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
In the present report, a case of a healthy, 38–year-old male recreational marathon runner who presented in the emergency department is discussed. He was diagnosed with a stress fracture of the femoral neck and treated surgically using a dynamic hip screw (DHS). One year after surgery, the patient was able to return to most of his previous sports activities. In the present report, the existing literature on the subject is exhibited and the points of interest in terms of incidence, risk factors, diagnosis, classification, treatment, and long-term outcome are analyzed. We suggest operative treatment of stress fractures of the femoral neck even in cases of complete undisplaced ones. This way, the risk of a displacement is counteracted, and patients can quickly return to daily activities without having to withstand long-term immobilization.
Keywords: femoral neck stress fracture; marathon; sports; stress fracture